(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background of the Study: Musculoskeletal foot aches always developing hassle for medical professionals. Medical doctors are suffering from MFP in plenty of amounts. The study aims to evaluate the causes of musculoskeletal foot pain (MFP) among medical professionals and determine the prevalence of MFP in this population. The study also aims to investigate the correlation between age, weight, and MFP in medical professionals. Method: This study is a cross-sectional descriptive investigation of musculoskeletal foot pain among medical professionals in one small hospital in Bihar, India. The population of the study is medical professionals in the hospital, aged between 25 and 65, who are suffering from musculoskeletal foot pain. The sample size of the study is 30 doctors. The inclusion criteria are that the participants must be suffering from musculoskeletal foot pain, willing to participate in the study, and present at the time of data collection. The exclusion criteria are that the participants must not have a severe musculoskeletal foot pain condition and must not be complaining of any kind of headache or dizziness. The data analysis method for the study is a musculoskeletal-based questionnaire survey design using the Foot Health Status Questionnaire, which will be distributed among the sample using simple random sampling and convenient sampling techniques. The study setting is one small hospital in Bihar, India. Results: This research to discover the correlation between age, weight, also FHSQ rankings. The analysis interpreted that both age and weight showed a moderate correlation with the FHSQ ratings. Within the 30 common doctors surveyed it's far calculated that a hundred % of them are affected by musculoskeletal foot pain. The prevalence charge of MFP in each male is 70%, women 30%, docs 30%, physiotherapists 30%, nurses 20%, and pharmacists 20%. Conclusion: Medical doctors go through more than one musculoskeletal foot pain that notably influences the work output. As we understand from our examination that they are exposed to a substantial kind of discomfort in their everyday lifestyles. This has a look at confirmed a prevalence charge of one hundred% of MFP on medical professionals. The incidence of musculoskeletal foot ache amongst medical doctors became maximum in decreased legs, and feet.